Polyamidoamine dendrimers: favorable polymeric nanomaterials for lipase activation - Elgharbawy, Amal A.M.; Syed Putra, Sharifah Shahira; Hayyan, Maan; Hayyan, Adeeb; Basirun, Wan Jefrey; Mirghani, Mohamed Elwathig Saeed; Wan Nawawi, Wan Mohd Fazli; Majrashi, Abdulrahman Abdulaziz; Alias, Yatimah; Mohd. Salleh, Hamzah; Tok, Tugba Taskin (Elsevier Ltd. All rights, 2020)
Dendrimers are highly branched synthetic macromolecules that offer promising prospects for utilizing them in broad applications. This study investigates the role of polyamidoamine (PAMAM) dendrimer for lipase-catalyzed reaction in aqueous solution. The hydrolysis of para-nitrophenyl palmitate (pNPP) by four different lipases was tested with PAMAM dendrimer with different generations (i.e., D0.0, D2.5, D3.0, and D4.0). The results showed that the activity of Rhizopus niveus lipase (RNL) was enhanced up to 375% with PAMAM dendrimer (D0.0). The optimum incubation conditions such as the temperature and coupling time of the lipase with D0.0 were 40 °C and 2 h, respectively. The behavior of lipases at different pH showed that RNL was mostly active at pH 7.0. Most lipases with D0.0 were enhanced at least two-fold compared to the control samples. Kinetic study showed that the RNL affinity was enhanced in the presence of PAMAM. FTIR spectra strongly suggest that hydrogen bonding and electrostatic interactions were the main types of bonding in the RNL and PAMAM system. Additionally, the molecular docking simulation of the system was exerted to evaluate and support the related compound, (i.e., D0.0) as a ligand interacted effectively with RNL based on the experimental activity. The cytotoxicity study revealed mild toxicity of the system which could serve as a potential target in nanomedicine for many applications such as cancer therapeutics.